RISK ANALYSIS OF CO EMITED FROM MOTOR VEHICLES TO PEOPLE LIVING AND DOING ACTIVITIES IN ROADSIDE (CASE STUDY: JOGJAKARTA’S MAIN STREETS) - Budihardjo, Mochamad Arief (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Air pollution problems have been progressively set attention to the world specifically in industrial countries recently. This problem not only gives affect at health like emphysema, bronchitis, and other  inhalation disease  but  also  makes  plants  and  property  destruction  that  causing  loss. Research  concerning  in the  level  of  risk  which  is  accepting  by  people  who  living  and  doing activities  in  roadside  which most  of  air  pollutants  come from  transportation  facilities  such  as motor  vehicles.  This  research focuses  on  CO  exposure  which  penetrates  the  body  through respiration.  There  are  four  steps  in this  research,  first,  hazard  identification  showing  CO concentration  in  15  sampling  locations resulting  highest  CO  concentration  is  equal  to  17.250 µg/m3;  second,  exposure  assessment involves  population  exposed  that  are  Pedi  cab  worker, parking  man,  and  cloister  merchant  to know  CO  intake  each  person  using  calculation  of  CO  intake range from 1,0703-2,6089 mg/kg . day; third, dose-response assessment to know what people  will  be  experiencing  if  exposed  by  CO    at certain  dose;  fourth,  risk  characterization resulting  that  risk  value/Hazard  Index  (HI)  less  than  1. This  research  concludes  that  CO concentration of most main streets in Jogjakarta do not adverse to people’s health who living and doing activities in roadside